Analytical Model of Rain-Wind Induced Vibration of High-Voltage Transmission Line - Chao Zhou; Yibing Liu (Advances in Mechanical Engineering, 2014)
Under rainfall conditions, rain-wind induced vibration occurs on high-voltage transmission line occasionally. This phenomenon is caused by raindrops hitting the high-voltage conductor with a certain velocity and suspends to the bottom surface of the high-voltage conductor. By action of wind velocity and high-voltage conductor's motion, some suspended raindrops will be blown away or shaken off. The remaining water may be reformed as upper rivulet and lower rivulet. Like the effect of icing galloping, this type of vibration can cause metal fatigue on fittings and towers, while its mechanism remains unknown. The objective of this paper is to validate an analytical model of rain-wind induced vibration of the high-voltage transmission line and to investigate the effect of wind velocity, rivulet motion, raindrop velocity, and time varying mass on the vibration amplitude. Taking Tuo-chang transmission line as an example, the analytical model is solved by Galerkin weighted residual method and central difference method. The numerical results are in agreement with the experimental data available in the literature. The analytical model enables more comprehensive understanding of the rain-wind induced vibration mechanism.